GASP XIII. Star formation in gas outside galaxies. Issue 4 (5th November 2018) - Poggianti, Bianca M; Gullieuszik, Marco; Tonnesen, Stephanie; Moretti, Alessia; Vulcani, Benedetta; Radovich, Mario; Jaffé, Yara; Fritz, Jacopo; Bettoni, Daniela; Franchetto, Andrea; Fasano, Giovanni; Bellhouse, Callum; et al.
ABSTRACT: Based on MUSE data from the GASP survey, we study the $\rm H\, α$ -emitting extraplanar tails of 16 cluster galaxies at z ∼ 0.05 undergoing ram pressure stripping. We demonstrate that the dominating ionization mechanism of this gas (between 64 per cent and 94 per cent of the $\rm H\, α$ emission in the tails depending on the diagnostic diagram used) is photoionization by young massive stars due to ongoing star formation (SF) taking place in the stripped tails. This SF occurs in dynamically quite cold H ii clumps with a median $\rm H\, α$ velocity dispersion $σ = 27\rm \, km\, s^{-1}$ . We study the characteristics of over 500 star-forming clumps in the tails and find median values of $\rm H\, α$ luminosity $L_{\rm H\, α } = 4× 10^{38}\, \rm erg\, s^{-1}$, dust extinction AV = 0.5 mag, star formation rate SFR$=0.003\, M_{\odot }\, yr^{-1}$, ionized gas density $n_e =52\rm \, cm^{-3}$, ionized gas mass $M_{\rm gas} = 4× 10^4 \, M_{\odot }$, and stellar mass $M_{*} = 3× 10^6\, M_{\odot }$ . The tail clumps follow scaling relations ( M gas − M *, L H α − σ, SFR- M gas ) similar to disc clumps, and their stellar masses are comparable to Ultra Compact Dwarfs and Globular Clusters. The diffuse gas component in the tails is ionized by a combination of SF and composite/LINER-like emission likely due to thermal conduction or turbulence. The stellar photoionization component of the diffuse gas can be due either to leakage of ionizing photons from the H ii clumps with an average escape fraction of 18 per cent, or lower luminosity H ii regions that we cannot individually identify.